Impact of Green Logistics on International Trade: An Empirical Study in Asia–Pacific Economic Cooperation - Le, Thu Hien; Nguyen, Huu Kien; Nguyen, Thanh-Vu-Linh; Khuat, Thi-Mai-Huong; Pham, Thi-Phong-Thu; Nguyen, Thuong-Lang (International Journal of Economics and Financial Issues, 2022)
Green logistics has been a trend in the world. This research evaluates the impact of green logistics on international trade among APEC nations over the period of 9 years (2010 – 2018). The research uses an augmented gravity model to investigate the effects of green logistics on international trade through the Environmental Logistics Performance Index (ELPI). The results show that exporting countries applying green logistics increase the export volume to other members of APEC. In the long term, importing countries engaging in green logistics increase trade volume with green logistics countries in APEC. With the aim of enhancing international trade, APEC countries must improve domestic logistics performance. Through those analyses, research proposes several recommendations to encourage nations and enterprises to apply green logistics effectively.